Sodium primary battery cathode material and preparation method thereof
Patent Information
- Application Number
- CN202611177324.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-16
AI Technical Summary
[0002]在一次性电池领域,早期的碳锌电池(勒克朗谢电池)性能差、易漏液
1、本发明提供的低钠一次电池正极电极材料NaxNiyMnzO2的制备方法,采用纳米砂磨结合高温固相煅烧的方法,在常温条件下,将钠源、镍源、α-MnO2按不同的摩尔比例混合,使用球磨机进行砂磨,由于材料粒径减小至100nm~200nm,在纳米尺度上达到均匀的混合状态,增加了比表面积和反应活性,缩短了固相扩散距离,从而提高了高温固相反应的速率和效率,降低了反应温度和时间,最终提升了产物的纯度、均匀性;制备工艺所采用的原料均为普通的化学原料,来源丰富、价格便宜、无毒无污染,符合绿色环保理念,也能在商业化生产过程 中为企业降本增效;另外,制备工艺中所用的设备简单,制备过程易于控制,无特殊设备要求,制备流程简单易行,极易实现规模化工业生产。
Smart Images

Figure CN122930892A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrode material preparation technology, and in particular to a sodium primary battery cathode material and its preparation method. Background Technology
[0002] In the field of disposable batteries, early carbon-zinc batteries (Lucronche batteries) had poor performance and were prone to leakage. The goal of alkaline battery development is to provide upgraded products with higher power, larger capacity, longer storage life, and better leakage resistance. Under the premise of "disposable use," the primary goals are extremely low cost, high reliability, and sufficient performance. Secondly, the abundance and low cost of sodium resources make it an excellent electrolyte choice besides potassium resources, which together form the basis for the low cost of the battery. Disposable batteries have a huge market, such as consumer remote controls, clocks, toys, emergency lighting, and medical equipment. These scenarios require batteries to be ready to use immediately, maintenance-free, and still have sufficient power after years of storage, and are extremely sensitive to cost.
[0003] Manganese dioxide is the cathode material for the vast majority of commercial sodium primary batteries (alkaline batteries), and its research and development has always revolved around "how to make MnO2 discharge more efficiently and stably". Manganese dioxide is abundant, inexpensive, environmentally friendly, and has a suitable redox potential, making it an ideal cathode material for primary batteries.
[0004] The study focuses on the effects of different crystal forms (e.g., α-, γ-, ε-, β-) of MnO2 on discharge performance and storage lifetime; introducing small amounts of other metal ions (e.g., Bi, Co, Ni, Fe) into the MnO2 lattice is of paramount importance; controlling the morphology, porosity, and specific surface area of MnO2 particles to increase the reaction interface and improve ion and charge transport; and developing the optimal ratio and mixing process with conductive agents such as graphite to reduce electrode internal resistance and ensure maximum utilization of active materials.
[0005] The development of sodium primary battery cathode materials is a progressive optimization process that continuously pursues higher performance, lower cost, and higher reliability within the framework of "single-use". For civilian alkaline batteries, the core of the research and development is low-cost, high-performance modified manganese dioxide, and the target market is the massive civilian consumer electronics market. Summary of the Invention
[0006] The purpose of this invention is to provide a sodium primary battery cathode material and its preparation method. The method uses nano-sand milling combined with high-temperature solid-state calcination, which has the advantages of small particle size, simple operation, low cost and easy industrial production. Furthermore, the prepared material can be used immediately without charging as an independent power source. At the same time, nickel and sodium are relatively abundant in the earth's crust, inexpensive, environmentally friendly, non-polluting and non-toxic.
[0007] According to the present invention, a sodium primary battery cathode material is provided, wherein the cathode material comprises a material with the general chemical formula Na. x Ni y Mn z O2 material, where 0.1≤x≤0.2; 0.1≤y≤0.2; 0.6≤z≤0.8.
[0008] The present invention also provides a method for preparing the sodium primary battery cathode material as described above, comprising the following steps: S1: Sodium source, nickel source and α-MnO2 are mixed in molar ratio and then milled until the particle size is reduced to 100nm~200nm to obtain powder; S2: The powder is compressed into tablets using a tablet press to obtain round, block-shaped solid samples; S3: Calcine the solid sample in a muffle furnace under an air atmosphere.
[0009] Furthermore, in step S1, the sodium source includes at least one of sodium carbonate, sodium hydroxide, sodium nitrate, sodium acetate, and sodium oxalate.
[0010] Furthermore, in step S1, the nickel source includes at least one of nickel suboxide, nickel tetroxide, nickel hydroxide, nickel trioxide, and nickel sulfate.
[0011] Furthermore, in step S1, the α-MnO2 raw material has a particle size of 100-150 nm.
[0012] Furthermore, in step S1, the grinding media are zirconium balls and solid powder, the mass ratio of zirconium balls to solid powder is 8:1 to 12:1, and the grinding time is 3h to 5h.
[0013] Furthermore, in step S2, the tablet press pressure is 30-50 MPa and the time is 10-20 s.
[0014] Furthermore, in step S3, the calcination temperature is 400℃~550℃, and the time is 5h~10h.
[0015] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. The low-sodium primary battery positive electrode material Na provided by this invention x Ni y Mn zThe method for preparing O2 employs a combination of nano-grinding and high-temperature solid-state calcination. At room temperature, sodium source, nickel source, and α-MnO2 are mixed in different molar ratios and then milled using a ball mill. Because the particle size is reduced to 100nm–200nm, a uniform mixing state is achieved at the nanoscale, increasing the specific surface area and reactivity, and shortening the solid-state diffusion distance. This improves the rate and efficiency of the high-temperature solid-state reaction, reduces the reaction temperature and time, and ultimately enhances the purity and uniformity of the product. The raw materials used in the preparation process are all common chemical raw materials, abundant in source, inexpensive, non-toxic, and pollution-free, conforming to the concept of green environmental protection and enabling cost reduction and efficiency improvement for enterprises in commercial production. Furthermore, the equipment used in the preparation process is simple, the process is easy to control, requires no special equipment, and the preparation flow is simple and easy to implement, making it highly suitable for large-scale industrial production.
[0016] 2. The Na prepared by this invention x Ni y Mn z O2 has a high energy density, does not require consideration of the limitations imposed on electrode structure by reversible charge and discharge, and has a relatively flat discharge curve with a small voltage drop throughout the discharge process. Attached Figure Description
[0017] Figure 1 The sodium primary battery positive electrode material Na provided in Embodiments 1, 2, 3, Comparative Example 1, and Comparative Example 2 of this invention x Ni y Mn z Discharge curve of O2 at a cutoff voltage of 1.8V. Detailed Implementation
[0018] To enable those skilled in the art to better understand the present application, the technical solutions of the present application will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only some embodiments of the present application, and not all embodiments. Based on the embodiments of the present application, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of the present application. Unless otherwise specified, the raw materials in the embodiments of the present application are all conventional products that can be purchased commercially.
[0019] This invention provides a sodium primary battery cathode material, the cathode material comprising the chemical formula Na x Ni y Mn z O2 material, where 0.1≤x≤0.2; 0.1≤y≤0.2; 0.6≤z≤0.8.
[0020] The present invention also provides a method for preparing the above-mentioned sodium primary battery cathode material, comprising the following steps: S1: Sodium source, nickel source and α-MnO2 are mixed in molar ratio and then milled until the particle size is reduced to 100nm~200nm to obtain powder; S2: The powder is compressed into tablets using a tablet press to obtain round, block-shaped solid samples; S3: Calcine the solid sample in a muffle furnace under an air atmosphere.
[0021] In step S1, the sodium source includes at least one of sodium carbonate, sodium hydroxide, sodium nitrate, sodium acetate, and sodium oxalate.
[0022] In step S1, the nickel source includes at least one of nickel suboxide, nickel tetroxide, nickel hydroxide, nickel trioxide, and nickel sulfate.
[0023] In step S1, the α-MnO2 raw material has a particle size of 100-150 nm.
[0024] In step S1, the grinding media are zirconium balls and solid powder, the mass ratio of zirconium balls to solid powder is 8:1 to 12:1, and the grinding time is 3h to 5h.
[0025] In step S2, the tablet press pressure is 30-50 MPa and the time is 10-20 s.
[0026] In step S3, the calcination temperature is 400℃~550℃, and the time is 5h~10h.
[0027] It is worth noting that the sodium source mentioned in this invention refers to a sodium-containing compound, the nickel source refers to a nickel-containing compound, and α-MnO2 refers to a specific crystal structure variant of manganese dioxide, which has a typical 2×2 tunnel structure.
[0028] This invention provides a method for preparing NaxNiyMnzO2, a positive electrode material for sodium primary batteries. The method employs nano-milling combined with high-temperature solid-state calcination. At room temperature, sodium source, nickel source, and α-MnO2 are mixed in different molar ratios and milled using a ball mill. This reduces the particle size to 100nm–200nm, achieving a uniform mixing state at the nanoscale. This increases the specific surface area and reactivity, shortens the solid-state diffusion distance, and thus improves the rate and efficiency of the high-temperature solid-state reaction, reducing the reaction temperature and time. Ultimately, this enhances the purity and uniformity of the product. The raw materials used in the preparation process are all common chemical raw materials, abundant, inexpensive, non-toxic, and pollution-free, conforming to the concept of green environmental protection and enabling cost reduction and efficiency improvement for enterprises in commercial production. Furthermore, the equipment used in the preparation process is simple, the process is easy to control, requires no special equipment, and the preparation flow is simple and easy to implement, making it highly suitable for large-scale industrial production.
[0029] The Na prepared by this invention x Ni y Mn z O2 belongs to the R3m space group structure, and its layered structure contains stable Na+. + The insertion / extraction channel is suitable for use as a positive electrode material; it discharges within a voltage window of 3.3V to 1.8V, with an average (median) discharge voltage of 2.81 to 2.6V and a specific capacity of 114mAh / g. Furthermore, the α-NaxNiyMnzO2 prepared by this invention has a high energy density, does not require consideration of the limitations of reversible charge / discharge on the electrode structure, and has a relatively flat discharge curve with a small voltage drop throughout the discharge process.
[0030] Example 1 This embodiment provides a positive electrode material for a sodium primary battery, specifically using orbital-type Na. x Ni y Mn z O2 has a structure space group of R3m.
[0031] The above-mentioned sodium primary battery positive electrode material is prepared according to the proportion of Na. 0.2 Ni 0.2 Mn 0.8 The specific steps for preparing O2 are as follows: Step 1: Using nickel oxide and sodium carbonate as nickel and sodium sources respectively, doping with α-MnO2, 14.94 g of nickel oxide, 10.6 g of sodium carbonate and 69.55 g of α-MnO2 (nickel / sodium / manganese molar ratio of 1:1:4) were mixed, and 104.6 g of zirconia beads with a particle size of 5 mm were used as the grinding media. The mixture was ball-milled in a ball mill for 3 hours until the particle size was reduced to 100 nm to 200 nm. The ball mill speed was 800 rpm (uniform speed). Step 2: Press the powder obtained from ball milling in step 1 into round solid blocks.
[0032] Step 3: Place the solid sample obtained in Step 2 in a muffle furnace and sinter at 450℃ for 9 hours, with a heating rate of 2℃ / min and an air atmosphere. After naturally cooling to room temperature, remove the sample and grind it to obtain orbital α-Na. 0.2 Ni 0.2 Mn 0.8 O2 sodium is a positive electrode material for primary batteries.
[0033] The above-mentioned sodium primary battery positive electrode material Na 0.2 Ni 0.2 Mn 0.8O2 is mixed with conductive agent (acetylene black) and binder (polyvinylidene fluoride, PVDF) at a mass ratio of 90:5:5. NMP is used as solvent. The mixture is ground to obtain a slurry. The slurry is then evenly coated onto the surface of the aluminum foil current collector with a scraper and dried at 120°C for 12 hours. The electrode is then cut into 12mm round pieces.
[0034] Using the aforementioned electrode as the positive electrode, a composite sodium sheet as the counter electrode, sodium perchlorate / EC+EWC+DEC as the electrolyte, and glass fiber (GF / D) as the separator, a CR2032 coin cell was assembled in a stainless steel argon atmosphere glove box with water and oxygen contents both below 0.01ppm. Electrochemical tests were conducted at room temperature (25℃±1℃) with a discharge cutoff voltage of 1.8V and a current density of 2mA / g.
[0035] Regarding Na in this embodiment 0.2 Ni 0.2 Mn 0.8 The O2 cathode material was tested for electrochemical performance at 2 mA / g, exhibiting a flat discharge curve. This was observed for the Na in this embodiment. 0.2 Ni 0.2 Mn 0.8 Analysis of the O2 self-discharge curve during the static period showed that after 9 hours of static discharge, the voltage remained at 3.3V, indicating extremely low self-discharge.
[0036] For Na in this embodiment 0.2 Ni 0.2 Mn 0.8 Analysis of the discharge curve of O2 shows that the voltage plateau during discharge is between 2.81 and 2.6V, indicating a stable discharge plateau.
[0037] Regarding Na in this embodiment 0.2 Ni 0.2 Mn 0.8 Analysis of the overall curve of O2 shows that when the voltage is discharged from 3.3V to 1.8V and the discharge rate is 2mA / g, its specific capacity can reach 114mAh / g.
[0038] Example 2 This embodiment provides a sodium primary battery positive electrode material, which is the same as in Embodiment 1.
[0039] This embodiment provides a method for preparing a sodium primary battery positive electrode material, the only difference from Embodiment 1 being that Na is used. 0.1 Ni 0.1 Mn 0.6 O2 feed ratio; After testing, the results showed that the primary battery cathode material still has similar electrochemical performance when discharged from 2mA / g to 1.8V, and its specific capacity can reach 110mAh / g.
[0040] Example 3 The only difference between this embodiment and Example 1 is that sodium hydroxide is used as the sodium source and nickel hydroxide is used as the nickel source. After testing, the results show that the positive electrode material of this primary battery still has similar electrochemical performance when discharged from 2mA / g to 1.8V, and its specific capacity can reach 109mAh / g.
[0041] Comparative Example 1 The only difference between Comparative Example 1 and Example 1 is that the solid sample obtained in step S2 was calcined in a muffle furnace at 300°C. After testing, the results showed that the primary battery cathode material had poor electrochemical performance when discharged from 2mA / g to 1.8V, with a specific capacity of only 51mAh / g.
[0042] Comparative Example 2 The only difference between Comparative Example 2 and Example 1 is that the solid sample obtained in step S2 was calcined in a muffle furnace at 600°C. After testing, the results showed that the primary battery cathode material had poor electrochemical performance when discharged from 2mA / g to 1.8V, with a specific capacity of only 44mAh / g.
[0043] The sodium primary battery positive electrode materials provided in Examples 1, 2, 3, Comparative Example 1, and Comparative Example 2 were mixed with a conductive agent (acetylene black) and a binder (polyvinylidene fluoride, PVDF) at a mass ratio of 90:5:5. NMP was used as a solvent, and the mixture was ground to obtain a slurry. The slurry was then uniformly coated onto the surface of an aluminum foil current collector with a scraper and dried at 120°C for 12 hours. The electrode was then cut into 12 mm round pieces.
[0044] Using the aforementioned electrode as the positive electrode, a composite sodium sheet as the counter electrode, sodium perchlorate / EC+EWC+DEC as the electrolyte, and glass fiber (GF / D) as the separator, a CR2032 coin cell was assembled in a stainless steel argon atmosphere glove box with water and oxygen contents both below 0.01ppm. Electrochemical tests were conducted at room temperature (25℃±1℃) with a discharge cutoff voltage of 1.8V and a current density of 2mA / g.
[0045] get Figure 1 Analysis of specific capacity discharge curve Figure 1 It can be seen that the raw materials used in Example 1, calcined at 450℃, produce a product with the best specific capacity under these conditions. Therefore, the conditions in Example 1 are suitable for preparing Na. x Ni y Mn zO2 primary battery cathode material; the data in Examples 2 and 3 are only slightly different from those in Example 1, proving that the material can also be prepared under the conditions of Examples 2 and 3; however, in Comparative Examples 1 and 2, only the calcination temperature was changed, but the data differences were large, proving that Na materials meeting the requirements could not be prepared under the conditions of Comparative Examples 1 and 2. x Ni y Mn z O2.
[0046] This demonstrates that the sodium-nickel-manganese composition ratio exhibits good robustness within the defined range (0.1≤x≤0.2; 0.1≤y≤0.2; 0.6≤z≤0.8). The substitution of different sodium and nickel sources has minimal impact on performance, proving the rationality of the equivalence and protection range listed by Markush. The overall data fully support the technical effect of this preparation method in obtaining high-capacity, low self-discharge, and stable discharge platform high-quality sodium primary battery cathode materials under the synergistic effect of low-temperature nano-sand milling.
[0047] Meanwhile, the calcination temperature is the most critical process parameter that determines the electrochemical performance of the cathode material. 450℃ is the optimal calcination point (with a specific capacity of 114 mAh / g), while a low temperature of 300℃ leads to insufficient solid-phase reaction, and a high temperature of 600℃ causes particle sintering or phase transformation, both of which cause the specific capacity to drop sharply to below 50 mAh / g. This strongly verifies the necessity and critical significance of the temperature range of 400℃ to 550℃ in the claims.
[0048] The above description is only a preferred embodiment of this application. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of this application, and these improvements and modifications should also be considered within the scope of protection of this application.
Claims
1. A sodium primary battery cathode material, characterized in that, The positive electrode material of the battery includes materials with the general chemical formula Na. x Ni y Mn z O2 material, where 0.1≤x≤0.2; 0.1≤y≤0.2; 0.6≤z≤0.
8.
2. A method for preparing the sodium primary battery cathode material as described in claim 1, characterized in that, Includes the following steps: S1: Sodium source, nickel source and α-MnO2 are mixed in molar ratio and then milled until the particle size is reduced to 100nm~200nm to obtain powder; S2: The powder is compressed into tablets using a tablet press to obtain round, block-shaped solid samples; S3: Calcine the solid sample in a muffle furnace under an air atmosphere.
3. The method for preparing a sodium primary battery cathode material according to claim 2, characterized in that, In step S1, the sodium source includes at least one of sodium carbonate, sodium hydroxide, sodium nitrate, sodium acetate, and sodium oxalate.
4. The method for preparing a sodium primary battery cathode material according to claim 2, characterized in that, In step S1, the nickel source includes at least one of nickel suboxide, nickel tetroxide, nickel hydroxide, nickel trioxide, and nickel sulfate.
5. The method for preparing a sodium primary battery cathode material according to claim 2, characterized in that, In step S1, the α-MnO2 raw material has a particle size of 100-150 nm.
6. The method for preparing a sodium primary battery cathode material according to claim 2, characterized in that, In step S1, the grinding media are zirconium balls and solid powder, the mass ratio of zirconium balls to solid powder is 8:1 to 12:1, and the grinding time is 3h to 5h.
7. The method for preparing a sodium primary battery cathode material according to claim 2, characterized in that, In step S2, the tablet press pressure is 30-50 MPa and the time is 10-20 s.
8. The method for preparing a sodium primary battery cathode material according to claim 2, characterized in that, In step S3, the calcination temperature is 400℃~550℃, and the time is 5h~10h.